2017
DOI: 10.4103/npmj.npmj_136_17
|View full text |Cite
|
Sign up to set email alerts
|

Urinary schistosomiasis in school children of a southern nigerian community 8 years after the provision of potable water

Abstract: The prevalence and intensity of S. haematobium have significantly reduced in this community though not yet eliminated. More boreholes need to be provided to make the water more accessible. This could be combined with other measures to eradicate S. haematobium from this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 1 publication
1
9
2
Order By: Relevance
“…Proteinuria and haematuria as morbidity markers of urogenital schistosomiasis were higher in prevalence in this study compared to reports from Southern and North Central Nigeria [14,47,49].…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Proteinuria and haematuria as morbidity markers of urogenital schistosomiasis were higher in prevalence in this study compared to reports from Southern and North Central Nigeria [14,47,49].…”
Section: Discussioncontrasting
confidence: 78%
“…Although the physiological, biochemical, immunological and prognostic roles of these markers in relation to urogenital schistosomiasis are yet to be ascertained [50], they have been reported to correlate with the presence and intensity of infection and could be employed as indirect diagnostic tools, as well as screening tools to monitor the progress of interventions directed at curtailing the disease [28,47,49,51]. Similar to previous reports, the intensity of infection among majority of the subjects with urogenital schistosomiasis in this study was light [15,47,49,52]. The implication of this finding is that, subjects in this study could be considered to be at a lower risk of infectionrelated morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth mentioning that a combination of microscopy, proteinuria and microhaematuria may be more efficient in infection diagnosis than a single variable. The prevalence of microhaematuria and proteinuria obtained in this study was lower than the 80 % and 56 % respectively reported in Ikpeshi in Akoko Edo LGA, Edo State (25); 80.3 % and 24.8 % proteinuria and microhaematuria respectively in Ijoun, Ogun State [34]; 65 % microhaematuria in Akinlalu and Ogbogba communities, Osun State [35]; Ekanem et al [36] reported decline in the microhaematuria and proteinuria [65.4 % to 23.6 % and 53.3 % to 54.5 % respectively] amongs in school children in Adim community in Cross River State eight years following the provision of portable water. The prevalence of schistosomiasis was 14.5% compared to 51% in the prepotable water era.…”
Section: Discussioncontrasting
confidence: 70%
“…Water-associated behaviors are possibly similar for very young males and females thereby leading to M:F prevalence of infection ratios closer to one. Whilst our initial aim had been to report data dis-aggregated by sex and age, we however found only 13 studies [20,23,29,44,45,55,[81][82][83][84][85][86][87], that reported prevalence of infection data in males and females, stratified by age. This was not a sufficient number of studies, or a sufficient level of detail, to conduct a robust analysis.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%